DAMPAK PERILAKU KONSUMEN TERHADAP PENGGUNAAN AKSES SITUS ON-LINE SHOP (STUDI KASUS PADA MAHASISWA DI UNIVERSITAS PANCASAKTI TEGAL) - Agnes Dwita Susilawati; Dewi Apriani Fr (UNIVERSITAS PGRI MADIUN, 2018)
ABSTRACTThe development of information technology has touched various joints of human life, especially the development of the internet. The development of the internet forms a new world where every individual has the right and ability to interact with other individuals indefinitely. The objectives of the research are (1) The influence of service quality on consumer satisfaction in accessing online shop website, (2) To know the influence of attitude and trust toward online shop shop user and (3) Influence of satisfaction to consumer loyalty online shop. Data analysis method used is included in the category of quantitative data analysis is a data analysis using statistical instruments. Statistical instruments used are Chi Square Test and performed using SPSS (Statistical Package For Social Science) software. The results of model fit testing showed that the four factors (cultural, economic, social and ethical) that have the most contigency coefficient on consumer behavior in accessing online shop site are Social variables. This means showing a group of people or individuals having a relationship between consumers with each other in choosing products through an online shop site and building good communication in choosing products and knowing the risks faced when buying products through online shop site.Keywords: Consumer Behavior, Use of On-Line Website Access Shop